Between the ideal conversion and “superficial” conversions: fluid boundaries between Christians, Jews and pagans in the Cyprian’s work (century III AD) - Soares, Carolline da Silva (Romanitas - Revista de Estudos Grecolatinos, 2014)
Our aim in this paper is to analyze the concept of conversion by Cyprian of Carthage. We intend to demonstrate that some Christian’s conversions were not sincere, especially in the mid third century persecutions historical context, a time of instability in the Empire. Given the obligation of worshiping pagan gods and denying their own faith in the courts, some Christians became known as lapsi – apostates. From this category, we intend to investigate the representations that Cyprian effects on it and to demonstrate through his remarks that among religious adherents of Christianity, paganism and Judaism the borders were still very tenuous, featuring what may be called a "superficial" conversion.